DAYA TERIMA KUE DONAT DAN PUKIS SUBSTITUSI TEPUNG UBI JALAR UNGU DAN TEPUNG KACANG HIJAU - Lydia fanny; Megawati Megawati; Fatmawaty Suaib (Media Gizi Pangan, 2019)
ABSTRACTOne of the problems which nutrition is still main in toddlers nutrition that is the problem a chronicle or called also stunting. Children suffer stunting due to lack of food intake and its diseases repeated especially of infection diseases which can increase metabolic needs and reduce appetite that has happened that abnormality in bodily form short although the genes into cells show the potential to grow. One way to solve the problem is stunting with consuming foods high in protein, local this research aims to review the receipt and macro nutrient analysis on the cake donuts and pukis with the substitution of flour sweet potato flour. purple and green beans. Resources i judged based on the panel against 30. hedonicThe results of the best nutritional value received analyzed the protein can use a method of micro kjedahl, fat soxhlet, analysis method and its luff schroll. carbohydrates analysis method. The research results show that the panel power received our foremost is f2 ( pukis ). Based on the aspect of the color of the most favored f2 ( pukis ) 73.3 %, as many as the aspect of the scent of f1 ( doughnuts ) 90 %, as many as the aspect of texture f2 ( pukis ) as much as 86.7 % and aspects of the f2 ( pukis ) 90 %. Nutritional content protein f1 ( doughnuts ) 8.43 %, as much as fat f1 ( doughnuts ) as much as 17.37 % and carbohydrates f1 ( doughnuts ) as much as 51.02 % while for nutritional content protein f2 ( pukis ) 7.37 %, as much as fat f2 ( pukis ) as much as 4.25 % and carbohydrates f2 ( pukis ) as much as 49.16 %. Keywords : Doughnut , green beans , pukis, sweet potato purple